VASYL STEFANYK’S BELLETRISTIC LANGAUGE IN IVAN KOVALYK’S SCIENTIFIC STUDIES - Greshchuk, V. V. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2020)
The article analyses Ivan Kovalyk’s studies of Vasyl Stefanyk’s belletristic language. The scholar’s novellas studies about functioning of similes, epithets, dialecticisms and anthroponyms in Stefanyk’s have been examined. The scientific basis of creation and principles of compiling of a “Dictionary of Language of Vasyl Stefanyk’s Belletristic Works”, performed by Ivan Kovalyk, have been comprehensively covered.